PENINGKATAN KETERAMPILAN DAN PRESTASI BELAJAR PESERTA DIDIK KELAS X AGRIBISNIS TERNAK UNGGAS PADA MATA PELAJARAN PENETASAN TELUR DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) DI SMK NEGERI 1 PANDAK - yulia (Jurnal Riset Daerah, 2023)
This type of research was classroom action research with research subjects being class XII students of Poultry Agribusiness SMK N 1 Pandak Bantul, Yogyakarta. This study consisted of two action cycles. Cycle I with basic competence in choosing hatching eggs, material for selecting duck eggs for hatching and cycle II with material for selecting chicken eggs for hatching. Data on aspects of students' skills were obtained from observations. Student achievement data was obtained from written tests, and the data obtained was analyzed using descriptive analysis. The results of this study showed that the level of skill mastery of students with very skilled criteria was 25.93% (7 pesdik), cycle I increased to 44.44% (12 pesdik), and in cycle II it increased to 65.67% (18 pesdik ) , so that there was an increase between the initial conditions and cycle I of 18.51% and between cycle I and cycle II there was an increase of 21.23%. The learning achievement of students in the initial conditions that reached the minimum completeness criteria was 5 students (18.52%), and in cycle I it increased to 21 students (77.78%), while in cycle II all students (100%) ) achieve the minimum completeness criteria. This means that there is an increase in the learning completeness of students from the initial conditions and cycle I of 59.26%, while an increase in learning completeness between cycle I and cycle II is 22.22%.